2019
DOI: 10.1088/1742-6596/1350/1/012181
|View full text |Cite
|
Sign up to set email alerts
|

Improvement the Bending Magnet Power Supply Performance for TPS Storage RING

Abstract: In the TPS (Taiwan Photon Source) facility, current stability of the electron beam depends on the bending magnet power supply and an orbit FOFB system to compensate the magnetic field. Due to the output current stability of the bending magnet power supply drifts with temperature so the orbit FOFB system should be applied to fine tune magnetic field and the photon beam should circulate in storage ring. In this paper, to stabilize the temperature of regulation circuit’s temperature box of the bending magnet powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…in Equation (5) gives a likelihood of cosmological parameters and SFE. For more detailed information of the data set, such as the redshifts and stellar masses of the candidate galaxies, we refer the readers to Wang et al (2023a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…in Equation (5) gives a likelihood of cosmological parameters and SFE. For more detailed information of the data set, such as the redshifts and stellar masses of the candidate galaxies, we refer the readers to Wang et al (2023a).…”
Section: Resultsmentioning
confidence: 99%
“…Labbé et al (2023) found six candidate massive galaxies (stellar mass 10 10 solar masses) at 7.4 z 9.1. This finding suggests that either the star formation efficiency (SFE) significantly exceeds its typical values in low-redshift galaxies, or the halo mass function is about 2σ higher than the prediction of the standard ΛCDM cosmology (Haslbauer et al 2022;Wang et al 2023a;Boylan-Kolchin 2023;Lovell et al 2023;Qin et al 2023). Although at the current stage a large SFE cannot be theoretically excluded (Zhang et al 2022;Qin et al 2023), a large SFE at z  7 tends to enhance the UV radiation from galaxies, causing a faster reionization process that is in tension with observation (Goto et al 2021;Wold et al 2022;Lin et al 2024).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations